2011
DOI: 10.5562/cca1721
|View full text |Cite
|
Sign up to set email alerts
|

Silica Chloride Nano Particle Catalyzed Synthesis of 2,2'-(arylmethylene)bis(5,5-dimethylcyclohexane-1,3-dione) Derivatives

Abstract: Abstract. Silica chloride nano particle (nano SiO 2 -Cl), has been found to be heterogeneous catalyst for facile and simple condensation of dimedone with aromatic aldehydes into 2,2'-(arylmethylene)bis(5,5-dimethylcyclohexane-1,3-dione) derivatives in dry CH 2 Cl 2 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…developed a choline chloride‐based deep eutectic solvent system at 80 °C, but the reaction time was long and a lower yield was obtained than in our system. Moghimi et al …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…developed a choline chloride‐based deep eutectic solvent system at 80 °C, but the reaction time was long and a lower yield was obtained than in our system. Moghimi et al …”
Section: Resultsmentioning
confidence: 99%
“…Hashemi et al [35] developed a choline chloride-based deep eutectic solvent system at 80°C, but the reaction time was long and a lower yield was obtained than in our system. Moghimi et al [36] used silica chloride nanoparticles as a catalyst with CH 2 Cl 2 as solvent, but the CH 2 Cl 2 is not environmentally friendly. Recently, Myrobh et al [37] demonstrated L-proline as a asymmetric catalyst in aqueous medium for the synthesis of pyrimidines and xanthenes.…”
Section: Synthesismentioning
confidence: 99%
“…Tetraketones were first described by Merling in 1894, during his pioneering work of synthesizing the cyclohexane‐1,3‐dione from resorcinol. Then, several reports have appeared to attempt efficient synthesis of tetraketones.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 A wide variety of Lewis acids have been used for organic transformations. 3 Most of the classical reagents of this class, such as AlCl 3 , BF 3 /BF 3 .…”
Section: Introductionmentioning
confidence: 99%